Arbitration's Century Milestone Shows A Path from Skepticism to Ubiquity. Issue 4 (30th March 2023) - Samuel, Adam
Abstract : On Sept. 24, 2023, please raise a glass to celebrate the centenary of the first truly international multilateral treaty on arbitration.